Images of Maria Regina in the 8th-Century Roman Painting - Lidova, Maria A. (Actual Problems of Theory and History of Art, 2024)
The paper is dedicated to the study of the Maria Regina iconography in Rome. The representations of Mary as Queen are well-attested in the West, yet they are extremely rare in the art of the Eastern Mediterranean. Notwithstanding this fact, the possibility that this iconography originated in the central territories of the Byzantine Empire and perhaps in Constantinople itself cannot be ruled out entirely. In fact, the similarities in the dipiction of garments in the earliest representations of Maria Regina, such as the mural in Santa Maria Antiqua, the icon of Santa Maria in Trastevere and the mosaic decoration of the oratory of John VII (705–707), with contemporary representations of the Byzantine emperors and empresses, point to the existence of close ties between two visual traditions. Over the course of the 8th century, the Maria Regina imagery continued to evolve, with the creation of numerous representations around the city, which include several murals in Santa Maria Antiqua, Madonna in the niche in the lower church of San Clemente and fragmentary remains of a painted decoration in Santa Susanna. While maintaining a recognizable resemblance to the earlier representations, 8th-century monuments differ from them in many respects. This concerns not only the visual representation of the image and the pictorial settings in which it appears, but also the positioning and the new, less significant, role assigned to the representations of Maria Regina within the church space. The analysis of the 8th-century decorations testifies to the transformation of the Maria Regina iconography characterized by a gradual simplification of the image and its distancing from the Byzantine visual tradition of that period.This work was accomplished with financial support of RFBR grant № 21-012-41005 “Jerusalem and Understudied Apocrypha in Slavonic Translations: Textology, History, and Doctrines”.
Keywords: Maria Regina; iconography of the Mother of God; cult of the Virgin; early medieval painting in Rome; Santa Maria Antiqua; eighth century